The study on customer satisfaction towards services provided by Batu Burok Beach Resort / Morliyati Mohammad - Mohammad, Morliyati (2001)
This study will focus on measuring customer satisfaction towards services provided by Batu Burok Beach Resort. A customer satisfaction survey on this service must be carried out in order to provide a better understanding of the current services performances and to give recommendation and suggestions to the management of Batu Burok Beach resort about the services. There are varieties of factors, which can effects on the customer satisfaction. The factors such as services, facilities and price. This study was conducted at Batu Burok Beach Resort, which is concentrated on the guest whose come to Batu Burok Beach Resort. The problem of the study is BBBR does not know the extent customer satisfaction on term of accommodation, functions and coffee house provided. In this research, the questionnaire was distributed to the selected respondent for gathered the data. SPSS software version 10.0 is used for data analysis and the data was interpreted in term of frequency distribution and cross tabulation.